EFEKTIVITAS PERATURAN SEKOLAH DALAM MEMBENTUK SIKAP DISIPLIN SISWA DI SMP IT PERGURUAN BAITI JANNATI TANJUNG MORAWA - Fajar Siregar, Ilham; Marpaung, Jamiluddin; Harahap, Hotni (Jurnal Ilmu Pendidikan Islam, 2025)
In fact, in the field, namely at SMP IT Perguruan Baiti Jannati Tanjung Morawa, it is still often found that some students have not shown a disciplined attitude towards school regulations such as not arriving on time, littering, wearing complete clothing, not going out while studying. This study aims to describe the implementation of schools in forming a disciplined attitude of students at SMP IT Perguruan Baiti Jannati. This study uses a qualitative approach with a descriptive method and field research type. The data sources of the study were homeroom teachers and subject teachers at SMP IT Perguruan Baiti Jannati. Data collection methods are Observation, interviews, and documentation. The data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of the study indicate that SMP IT Perguruan Baiti Jannati Tanjung Morawa in the effectiveness of school regulations in forming a disciplined attitude of students of SMP IT Perguruan Baiti Jannati Tanjung Morawa through the habit of arriving on time, littering, wearing complete clothing, not leaving the classroom while studying and giving punishments or sanctions to male and female students who violate according to the violations committed.